2008
DOI: 10.1183/09031936.00143507
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive positive pressure ventilation in the acute care setting: where are we?

Abstract: Noninvasive positive pressure ventilation (NPPV) is a technique used to deliver mechanical ventilation that is increasingly utilised in acute and chronic conditions. The present review examines the evidence supporting the use of NPPV in acute respiratory failure (ARF) due to different conditions. Strong evidence supports the use of NPPV for ARF to prevent endotracheal intubation (ETI), as well as to facilitate extubation in patients with acute exacerbations of chronic obstructive pulmonary disease and to avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 161 publications
3
130
0
7
Order By: Relevance
“…A very severe life-threatening episode requires direct admission into the ICU. Several prospective randomised controlled studies, systematic reviews and metaanalyses show a good level of evidence for clinical efficacy of NPPV in the treatment of acute-on-chronic respiratory failure due to AECOPD [104]. Compared with standard medical therapy alone, NPPV improved survival, reduced the need for endotracheal intubation and the rate of complications, and shortened the hospital and ICU length of stay.…”
Section: Nppv In Aecopdmentioning
confidence: 99%
“…A very severe life-threatening episode requires direct admission into the ICU. Several prospective randomised controlled studies, systematic reviews and metaanalyses show a good level of evidence for clinical efficacy of NPPV in the treatment of acute-on-chronic respiratory failure due to AECOPD [104]. Compared with standard medical therapy alone, NPPV improved survival, reduced the need for endotracheal intubation and the rate of complications, and shortened the hospital and ICU length of stay.…”
Section: Nppv In Aecopdmentioning
confidence: 99%
“…There has been a similar historical trend in other European countries. 9,[17][18][19][20] The increasing popularity and effectiveness of NIV in ARF of various etiologies, [10][11][12] and the possibility of treating COPD exacerbations 4 with NIV in the RHDCU with the same likelihood of success and with lower costs than in an ICU, have contributed to the growth of RHDCUs. 9,15,16 According to the recent European survey, 9 Italy was the country with the highest number of RHDCUs.…”
Section: Number Geographic Distribution Institutionmentioning
confidence: 99%
“…9 This paralleled the expanding popularity of noninvasive ventilation (NIV) to treat ARF. [10][11][12] The 68 European surveyed units were classified into 3 levels of care, depending on the resources, the severity of the ARF, and the complexity of the available interventions: respiratory monitoring units (RMUs), respiratory intermediate intensive care units (RIICUs), and respiratory intensive care units (RICUs). 9 In agreement with these European data, in Italy there has been increasing interest in intensive care medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating body positioning and obesity-associated hypoventilation in patients undergoing NPPV showed that these factors may affect inspiratory and expiratory pressures to achieve a better minute ventilation (MV) [4][5][6]. Patient's comfort and adherence can be improved with the appropriate use of NPPV [7,8]. For an effective NPPV, an adequate MV should be sustained after selecting an appropriate mode; air leaks in the circuit should be minimized; and the patient-ventilator synchrony must be optimized [9,10].…”
Section: Introductionmentioning
confidence: 99%